Periodic waves in microstructured solids and inverse problems - Sertakov, Ivan; Janno, Jaan (Mathematical Modelling and Analysis, 2012)
Conditions for the existence of periodic and solitary waves in 1D microstructured solid of Mindlin type are deduced. Inverse problems to determine material properties are solved.